Improving Students’ Speaking abilities In The English Classroom Using Drama Method - Franscy; Dewi, Yuli Ani Setyo; Hudaa, Syihaabul; Wajdi, Muh. Barid Nizarudin; Istianingrum, Rika (International Journal of Psychosocial Rehabilitation, 2020)
this article aims to improve students’ speaking skills which were indicated by the increase of their speaking score. This technique can increase students’ confidence to speak in front of the public because the chronological procedures accommodate their social awareness. This research method used the Qualitative Method. The data from the classroom observation in the form of field notes were used to identify the teacher’s performance during the speaking classes. The research finding and discussion based on the two research questions formulated in this study. The first section was the answer to the first research problem. The second section provided the answer to the second research problem.